2005
DOI: 10.3755/jcrs.2005.1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diversity of Sarcophyton soft corals in Okinawa

Abstract: A total of 279 specimens belonging to nine species of soft corals of the genus Sarcophyton were subjected to chemical study for the diversity of cembrane diterpenes. Following morphological identification, each specimen was examined for metabolites using gradient HPLC, NMR, and other tools. The S. glaucum and S. cinereum species complex was found to be the most abundant and to contain the most diverse metabolites in the Ryukyu Archipelago, Japan. S. trocheliophorum and S. ehrenbergi were moderately abundant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…The isolation of only three metabolites 20 – 22 (Fig. 2) in their study would correlate with the results of Tanaka et al [52], showing the less complex metabolome of S. trocheliophorum . Exact identification of soft corals is, however still difficult and misidentification cannot be ruled out.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The isolation of only three metabolites 20 – 22 (Fig. 2) in their study would correlate with the results of Tanaka et al [52], showing the less complex metabolome of S. trocheliophorum . Exact identification of soft corals is, however still difficult and misidentification cannot be ruled out.…”
Section: Discussionsupporting
confidence: 89%
“…Other closely related soft corals, such as Lobophytum spp., also contain cembranoids, e.g., the isosarcophytoxides 10 and 11 [36] as well as a numerous biscembranoid compounds [51]. Distinct patterns of chemotypes in Sarcophyton species were demonstrated in a study by Tanaka et al [52]. In this latter study, the largest diversity of secondary metabolites was found for S. glaucum , compared with the moderate chemical diversity found in S. trocheliophorum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data may link all of the main carbons in cembranoid ring of all isolated compounds. The specific configuration of each compound was found with direct H2BC couplings of carbon with C-13 hydroxyl to H-14 (the same couplings with on the other way around) for sarcophytol B (1), H2BC couplings of epoxide between C-12 to H-11 for 11,12-epoxy sarcophytol A (2), tertiary C-14 with hydroxyl for Sarcophytol A, and quaternary C-1 with hydroxyl for Sarcophytol M. All of the isolated compounds in this study was already characterized previously by Kobayashi, Nakagawa, & Mitsuhashi, (1979) and Kobayashi & Osabe (1989 • 11,12-epoxy sarcophytol A (2) • Sarcophytol M (4) The f inding of sarcophytol A as the major cembranoid compound in Sarcophyton sample was also detected by previous study on the same genus, which are S. crassocaule, S. digtitatum, S. infundibuifurme, and S. glaucum (Koh et al, 2000;Tanaka, Yoshida, & Benayahu, 2005). Meanwhile, Sarcophytol M as a minor sarcophytol analogue was also found from a previous study on S. glaucum (Kobayashi & Osabe, 1989).…”
Section: Resultssupporting
confidence: 50%
“…Sarcophine present almost in all Sarcophyton genuses, which are S. glaucum, S. trocheliophorum, S. ehrenbergi, S. elegans, S. infundibuliforme, S. pulchellum, S. cherbonnieri, except in S. crassocaule and S. digitatum (Tanaka, Yoshida, & Benayahu, 2005). S. glaucum sub-species (clade A-F) can be also detected by specific cembranoid content that consists with sarcophine enantiomers (2S,7S,8S-sarcophine, 2S,7R,8R-sarcophine, or 2S,7R,8R-isosarcophine) and sarcophytolide cembranoid analogues (Aratake et al, 2012).…”
Section: Resultsmentioning
confidence: 99%